Model Bera dalam Sistem Agroforestri (Fallow Land Model in Agroforestry Systems) - Priyono Suryanto; WB. Aryono; M. Sambas Sabarnurdin (Jurnal Manajemen Hutan Tropika, 2006)
The development of tree-based agroforestry model gives consequences to the space utilization dominated by trees. Farmers take action on this condition by conniving the fallow land. This research was aimed to know the fallow land model, find the key parameters of fallow land model, and formulating the management of fallow land. The spatial model of agroforestry used in this research were trees along border, alley cropping, alternate rows and mixer. The actual data obtained were tree height, tree diameter, crown diameter, land width, and light intensity; the calculated data were land extent, the percentage of crown cover and crown density. The analysis used to determining the percentage of crown cover to calculate the affective arable land area was zone system. Zonation system maked for four zone : 1) zone 1 interval 0-1 m ; 2) zone 2 interval 1-2 m; zone 3 interval 2-3 m; zone 4 interval 3-4m.Key words: agroforestry, fallow land, silviculture, land cover, resource sharing, crown dynamic